Untersuchung zur Vererbung des Sommerekzems beim Islandpferd - Lange, Susanne (Tierärztliche Hochschule, 2004)
The objectives of the present study were to quantify the importance of systematic environmental and genetic influences on the prevalence and severity of summer eczema in Icelandic horses. In the context of this study, 490 Icelandic horses from 24 stud farms located in Lower Saxony and Westphalia were included. All horses on the stud farms were examined for the specific signs of summer eczema and the individual management conditions were documented. The study revealed a prevalence of summer eczema of 29.8 %. Mares were more often affected by summer eczema (33.1 %) than geldings or stallions with 29.1 % and 15.5 %, respectively. The most common sites of summer eczema were mane and tail. Icelandic horses born in Germany were significantly less affected than horses born in Iceland. The frequency of affected horses significantly increased with higher age and decreased with the number of years which had elapsed since importation. The onset of disease for imported horses was on average 2.5 ± 2.3 years after importation. Chestnut horses had a lower prevalence for summer eczema than horses with other coat colours, but they showed significantly more severe signs of summer eczema. In horses imported from Iceland, the inbreeding coefficient significantly influenced the prevalence of summer eczema. Housing of the horses during the night, the kind of combination of feeding ration in summer and winter and humid environments in the closer neighbourhood were significant influences on the prevalence of summer eczema. Stabling of horses in boxes, open stables or stables with paddocks were significantly related with the severity of summer eczema. The heritability estimate for the frequency of summer eczema using a linear animalmodel was h2 = 0.36 ± 0.08. The heritability estimate for the severity of symptoms of summer eczema using a linear animal model was h2 = 0.34 ± 0.09. The results of this study could show that a genetic component is responsible for summer eczema in horses. Ziel dieser Arbeit war es zu untersuchen, ob eine ...